2021
DOI: 10.6007/ijarbss/v11-i9/11081
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perception towards Online Distance Learning(ODL) during COVID-19 Pandemic in Undergraduate Students of Faculty of Health Science

Abstract: The educational system in Malaysia, including schools, colleges, and universities, is based on a traditional system. The outbreak of COVID-19 has an impact on the educational system across the world because it was forced to shut down during pandemics and changed from traditional methods to online and distance learning(ODL) or non-face to face. Due to this nature, COVID-19 tremendously affected the personal interaction of lecturers and students. The absence of traditional classroom teaching and computer-based l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The interaction definitely became difficult as ODL emphasises selfcentred learning and also because of the use of ICT, which not every student is familiar with. This finding was similar to studies by Ismail et al [19] and Almahasees et al [21], which also reported the lack of interactions in online learning caused by technical issues and limited time.…”
Section: Students' Perception Towards Open and Distance Learningsupporting
confidence: 92%
See 1 more Smart Citation
“…The interaction definitely became difficult as ODL emphasises selfcentred learning and also because of the use of ICT, which not every student is familiar with. This finding was similar to studies by Ismail et al [19] and Almahasees et al [21], which also reported the lack of interactions in online learning caused by technical issues and limited time.…”
Section: Students' Perception Towards Open and Distance Learningsupporting
confidence: 92%
“…Students and fellow educators from fulltime courses had to experience the nature of ODL without a proper planning and readiness. In the local context, Ismail et al [19] studied students' perception towards ODL during the pandemic. The study was conducted at Universiti Teknologi MARA (UiTM), with 265 diploma students from various programmes in the Faculty of Health Science.…”
Section: Introductionmentioning
confidence: 99%